Life cycle assessment and life cycle cost analysis of a 40 MW wind farm with consideration of the infrastructure. (March 2021) - Li, Qiangfeng; Duan, Huabo; Xie, Minghui; Kang, Peng; Ma, Yi; Zhong, Ruoyu; Gao, Tianming; Zhong, Weiqiong; Wen, Bojie; Bai, Feng; Vuppaladadiyam, Arun K.
Abstract: Wind power is being used on a large scale worldwide. While a few studies have employed the life cycle assessment method to examine the economic and environmental trade-offs of wind power, the impacts of wind farm infrastructure—such as civil and electrical works—have not been thoroughly taken into consideration. Thus, it remains difficult to accurately grasp the entire environmental impacts of wind energy systems. In this study, a newly built onshore 40-megawatt (MW) wind farm in China has been selected for conducting life cycle analysis with consideration of the infrastructure. Resource and energy-related inventory data were gathered over the wind farm's life cycle, including the phases of materials and manufacturing, transport, construction and installation, operations, and end-of-life. The results showed that the entire greenhouse gas emissions intensity was 16.4–28.2 gCO2 eq./kWh for the onshore 40 MW wind farm, which is slightly higher than those for nuclear power (10.9–13.9 gCO2 eq./kWh) and hydropower (3.1–3.9 gCO2 eq./kWh). It is almost comparable than photovoltaic power (16.0–40.0 gCO2 eq./kWh), but significantly lower than those for thermal power (810–820 gCO2 eq./kWh) and biomass power (~200 gCO2 eq./kWh). Additionally, life cycle cost analysis indicated that the levelized cost of electricity from wind power was approximately 0.01–0.02 USD/kWh. Highlights: Life cycle (and cost) assessment was performed for a regular onshore 40 MW wind farm in China. LCI data were gathered for the overall life cycle, particularly the construction phase. Whole life cycle GHG emissions intensity was 16.4–28.2 g CO2 eq./kWh. The emissions intensity of wind power was higher than those of nuclear and hydropower. Strategies for continually improving the environmental performance of wind power are discussed.